2018
DOI: 10.1007/978-3-030-01054-6_44
|View full text |Cite
|
Sign up to set email alerts
|

Information Gain Based Term Weighting Method for Multi-label Text Classification Task

Abstract: In text classification, terms are given weights using Term Weighting Scheme (TWS) in order to improve classification performance. Multi-label classification task are generaly simplified into several single-label binary task. Thus, the term distribution are considered only in terms of positive and negative categories. In this paper, we propose a new TWS based on the information gain measure for multi-label classification task. This TWS try to overcome this shortness without affecting the complexity of the probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In literature, there are many feature selection metrics. Some of them are used term weighting purpose like IG and CHI, some of them are used for feature selection like Term Frequency-Inverse Document Frequency (TF-IDF) originated from the term weighting method [10][11][12][13]. Relevance Frequency (RF) is another term weighting metric.…”
Section: Contribution and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there are many feature selection metrics. Some of them are used term weighting purpose like IG and CHI, some of them are used for feature selection like Term Frequency-Inverse Document Frequency (TF-IDF) originated from the term weighting method [10][11][12][13]. Relevance Frequency (RF) is another term weighting metric.…”
Section: Contribution and Motivationmentioning
confidence: 99%
“…In Equation ( 12), precision value (π ) and in Equation ( 13), recall value (ρ) are given. π = TP TP + FP (12) ρ = TP TP + FN (13) F-measure is given in Equation (14).…”
Section: Experimental Settingsmentioning
confidence: 99%
“…Unsupervised TWSs are generally borrowed from Information Retrieval domain [26] and adopted for TC [22,7,23].…”
Section: Term Weighting Schemesmentioning
confidence: 99%
“…Several comparative studies on these TWSs for both term-weighting and feature selection has been reported in [31,24,8,22]. A new approach for term-weighting based on (TF-IG) have been proposed for multi-labeled classification task in [23]. The method computes a score based on all categories and then subtracts it from the original TF-IG weight.…”
Section: Term Weighting Schemesmentioning
confidence: 99%